KARAKTERISASI MANIFESTASI TERMAL MENGGUNAKAN METODE RASIO SALURAN, LAND SURFACE TEMPERATURE, DAN NORMALIZED DIFFERENCE VEGETATION INDEX DI LAPANGAN PANAS BUMI GUNUNG PAPANDAYAN, JAWA BARAT: CHARACTERIZATION OF THERMAL MANIFESTATION USING BAND RATIO, LAND SURFACE TEMPERATURE, AND NORMALIZED DIFFERENCE VEGETATION INDEX METHODS IN PAPANDAYAN MOUNTAIN GEOTHERMAL FIELD, WEST JAVA - Satriyo, Muhammad; Fadillah Azhar Deaudin Kurniawan; Tony Rahadinata; Santia Ardi Mustofa (Buletin Sumber Daya Geologi, 2025)
The research area is located in the Gunung Papandayan Geothermal Field, which is interesting to study further due to several thermal manifestations found on the surface. However, a detailed remote sensing study accompanied by field validation has never been conducted in this field. Thus, this study aims to conduct a more detailed remote sensing analysis to describe the characteristics of thermal manifestations in the field that can be a reference for direct observation and support analysis in detailed geoscience studies. The remote sensing analysis performed is visual image analysis, surface temperature analysis, vegetation stress analysis, and band ratio analysis. The results showed that thermal manifestations can be found in the Papandayan Crater and Tegal Alun areas. The presence of manifestations is characterized by areas that have little to no vegetation in visual image observations, high land surface temperature (LST) anomalies, and normalized difference vegetation index (NDVI) values less than 0.3. Meanwhile, alteration minerals were identified from several band ratio analyses conducted.